Human Tooth and Developmental Dental Defects - Compositional and Genetic Implications 2022
DOI: 10.5772/intechopen.99542
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matrix of Enamel and Dentin and Developmental Defects

Abstract: The anatomical crown of the tooth is covered by enamel and root is covered by cementum. The dentin forms the major part of the tooth. The dentin structure is very similar to that of the bone both physically and chemically which is why many scientists have wondered about using its properties for developing a novel bone graft material. In contrast with hard and brittle enamel dentin is viscoelastic. The organic structure of dentin which is about 35% is composed of mainly type I collagen embedded in mucopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The average size of HAP is larger in enamel than dentine, which makes the former more calcified. In addition, enamel contains 95% inorganic material, 1% organic material, and 4% water by weight percentage, whereas dentin is composed of 70% inorganic material, 2% organic material, and 10% water by weight percentage [28][29][30]. Hence, the compositional analysis revealed that enamel has a lower concentration of water and higher mineral content (than dentin) which makes it difficult to ablate.…”
Section: Discussionmentioning
confidence: 99%
“…The average size of HAP is larger in enamel than dentine, which makes the former more calcified. In addition, enamel contains 95% inorganic material, 1% organic material, and 4% water by weight percentage, whereas dentin is composed of 70% inorganic material, 2% organic material, and 10% water by weight percentage [28][29][30]. Hence, the compositional analysis revealed that enamel has a lower concentration of water and higher mineral content (than dentin) which makes it difficult to ablate.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel comprises 96% inorganic material with the remaining 4% attributed to organic material and water. 10,50 Proteins make up 1%-2% of enamel's total composition. 10,50 Dentine composition resembles that of bone: it consists of 65% inorganic compounds and 35% organic materials and water.…”
Section: Absorption Features Specific To Hapmentioning
confidence: 99%
“…Tooth enamel is a complex mineralized tissue consists of 96 % inorganic and 4 % organic and water content, comprising of long and parallel apatite crystals configured into decussating enamel rods (Pandya & Diekwisch, 2019). On the other hand, dentin is a more complex dental substrate consists of 70 % inorganic phase in which carbonated calcium phosphate micro-crystals are located within an organic matrix that forms 20 % of dentin, the remainder 10 % is water (Lee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%